Disparities in Access to a Regular Primary Care Physician Among First-Generation Migrants with Early Psychosis in Ontario, Canada. - Valdez, Crystal; Rodrigues, Rebecca; Reid, Jennifer; Anderson, Kelly K. (Community Mental Health Journal, 2024)
Disparities in primary care utilization among migrants with early psychosis may be related to lack of access to a regular primary care physician. This study aimed to investigate access to a regular primary care physician among first-generation migrants with early psychosis. People aged 14–35 years with first onset non-affective psychotic disorder in Ontario, Canada were identified in health administrative data (N = 39,440). Access to a regular primary care physician through enrollment in the year prior to diagnosis was compared between first-generation migrants (categorized by country of birth) and the general population using modified Poisson regression. Most migrant groups had a lower prevalence of regular primary care physician access relative to the general population, particularly migrants from Africa (African migrants: 81% vs. non-migrants: 89%). Adjustment for sociodemographic and clinical factors attenuated these differences, although the disparities for migrants from Africa remained (PR = 0.96, 95%CI = 0.94–0.99). Interventions aimed at improving primary care physician access in migrant groups may facilitate help-seeking and improve pathways to care in early psychosis.